Properties of construction material based-Diss fibers: Physico-mechanical characterisation - Ismahen Zaid; Mouloud Merzoud; Amar Benazzouk (Journal of Building Materials and Structures)
In the building sector, issues related to sustainable development have become a major concern. The choice of materials has fundamental importance since it has a considerable influence on the energy consumption of the building and also on the overall environmental impact of the construction. Materials reinforced with vegetable fibres and/or particles are currently considered amongst the most promising materials in sustainable engineering technologies due to their several potential applications. In addition to its sustainable credentials, the application of these elements is interesting as they exhibit a set of important advantages, such as wide availability at relatively low cost, bio-renewability, ability to be recycled, biodegradability, non-hazardous nature, zero carbon footprint, and interesting hygro-thermal and mechanical properties.